Economic Rationale for the Proposed Bridge Between India and Sri Lanka: An Analytical Perspective - Gayasha Sathsarani, S.; Sarvananthan, M. (Taylor & Francis Group, 2023)
The Governments of India and Sri Lanka signed a Memorandum of Understanding (MoU) to build a bridge across the Palk Strait in July 2002 to join the island nation with the mainland of South Asia by road and rail. The objective of this article is to highlight the likely impact the proposed bridge would have on trade in goods and services and travel between the two countries and beyond. The overall argument herein is that any development activity would have positive and negative outcomes and that on a balance of probability, the positive outcomes of the proposed bridge could outweigh the negative outcomes. The proposed bridge across the Palk Strait could be an alternative to the proposed Sethusamudram project (that could potentially cause environmental damage) rekindled by the Tamil Nadu state assembly in January 2023 in order to stimulate economic growth in the lagging southern parts of Tamil Nadu.